2010
DOI: 10.1016/j.transproceed.2010.02.097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Partial Liver Ischemia Followed by Global Liver Reperfusion on the Remote Tissue Expression of Nitric Oxide Synthase: Lungs and Kidneys

Abstract: Hepatic ischemia followed by reperfusion (IR) results in mild to severe remote organ injury. Oxidative stress and nitric oxide (NO) seem to be involved in the IR injury. Our aim was to investigate the effects of liver I/R on hepatic function and lipid peroxidation, leukocyte infiltration and NO synthase (NOS) immunostaining in the lung and the kidney. We randomized 24 male Wistar rats into 3 groups: 1) control; 2) 60 minutes of partial (70%) liver I and 2 hours of global liver R; and 3) 60 minutes of partial (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 19 publications
1
31
0
2
Order By: Relevance
“…In the present study, the grades at which greatest endothelial damage occurred were the same as those in which morphological studies from this laboratory have shown evidence of endothelial injury and death (18). In other situations, such as vascular changes associated with endotoxic shock (29), and ischemia-reperfusion injuries (30), endothelial iNOS expression has been associated with endothelial damage mediated by free radicals. All of our data indicate a similar process in patients with extensive pulmonary fibrosis, and this situation contributes to maintenance of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the grades at which greatest endothelial damage occurred were the same as those in which morphological studies from this laboratory have shown evidence of endothelial injury and death (18). In other situations, such as vascular changes associated with endotoxic shock (29), and ischemia-reperfusion injuries (30), endothelial iNOS expression has been associated with endothelial damage mediated by free radicals. All of our data indicate a similar process in patients with extensive pulmonary fibrosis, and this situation contributes to maintenance of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms underlying this response are poorly understood. 3 IR injury of the liver has two distinct phases that contribute to hepatocyte damage. The acute phase is characterized by Kupffer cell production of reactive oxygen species (ROS) which results in moderate hepatocyte injury.…”
Section: Introductionmentioning
confidence: 99%
“…This induces different levels of tissue damage, and these injuries still develop during reperfusion. Hepatic ischemia/reperfusion frequently leads to remote organ injury [5]. In our preliminary experiment, 60 min of partial liver ischemia in addition to BDL led to death of most of the rats during the 24-h reperfusion, so the ischemia time was reduced to 30 min.…”
Section: Discussionmentioning
confidence: 82%